LANGUAGE POLICY AND EDUCATIONAL EFFECTIVENESS: AN EMPIRICAL STUDY BASED ON CLASSROOM OBSERVATIONS - Abduvaliyeva Sevinch Gaybullo kizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Language policy plays a crucial role in improving educational effectiveness and strengthening national identity. This study explores how language policy implementation influences students’ learning outcomes in educational settings. The research combines literature analysis with classroom-based observations and survey data collected from secondary school students. The findings indicate that the use of the native language as a medium of instruction significantly improves comprehension and student engagement. The study also highlights the importance of integrating digital resources and interactive teaching methods to strengthen language policy implementation in education.